Historical Pollution in the Polluter Pays Principle: Who Pays When the Polluter Is No Longer There? - Davilla Prawidya Azaria; Anni Alvionita Simanjuntak (Veteran Law Review, 2026)
The conventional Polluter Pays Principle encounters jurisdictional paralysis when confronted with historical pollution, particularly when responsible corporations escape liability through liquidation or strategic bankruptcy, leaving behind severely deteriorated environments as orphan sites. This normative legal research aims to formulate a policy reconstruction to bridge this intertemporal liability gap by analyzing successful environmental policy frameworks from various developing countries. Grounded in the protective function of state authority, governments possess an inherent responsibility and institutional capacity to proactively intervene in long-standing ecological crises. The analysis indicates that transferring remediation liability to the state can be effectively operationalized through adaptable instruments tested in the Global South, including state-led emergency restoration mechanisms, collective industry-funded environmental pools, and property-attached ecological obligations. In conclusion, the state must act as the primary executor of physical remediation upfront, subsequently utilizing its sovereign right to reclaim restoration costs from successor entities or parent companies to guarantee intergenerational ecological justice.